Convection in deep vertically shaken particle beds. I. General features - Sakon Klongboonjit; Charles S. Campbell (My University, 2008)
It has long been known that shaking a granular bed can produce circulating convection. This is the first in a series of papers that explores convection in beds a hundred particles or more deep. In such deep beds, the pressures are high enough that the particles remain in contact with their neighbors throughout much of the vibrational period. As such, they interact elastically and convection becomes dependent on the elastic properties of the bed. Changing the particle stiffness can dramatically alter the convection, and for very soft or very hard particles, eliminate it completely. In this paper, the effect of stiffness, bed geometry, and frictional properties on the global convection properties are assessed.
Keywords: Particle (ecology); Convection cell; Deep convection; Granular flow and fluidized beds